Development policy of the European Union - Holland, Martin, 1954-; Doidge, Mathew, 1976- (New York : Palgrave MacMillan, 2012)
'Designed to replace the same author's The European Union and the Third World, this new text provides systematic coverage of the European Union's policies in relation to the developing world in the twenty-first century and includes substantial coverage of governance issues and the relationship between development initiatives and European integration'--
Machine generated contents note: -- Introduction: Setting the Context * Four Decades of African, Caribbean and Pacific Relations * Latin America * Asia * Complementarity and Conditionality: Evaluating Good Governance * Regimes, Trade Policy and Trading Relations * Institutions, Reform and Aid * 2020 - The Cotonou Partnership Agreement * Implementing EPAs and'Everything but Arms' * The EU and the Global Governance Development Agenda * Development, Foreign Policy and EU Public Opinion * Conclusion: Development and Integration.
Include index and bibiliography : p. 249 -263.
Keywords: European Union countries -- Foreign economic relations -- Developing countries; Developing countries -- Foreign economic relations -- European Union countries